Genç yetişkinlerde fiziksel aktivite ve bilişsel performans arasındaki ilişkinin incelenmesi - Tekkuş, Bağdat (ADAMOR Toplum Araştırmaları Merkezi, 2021)
Fiziksel aktivitenin sağlığın birçok alanında kanıta dayalı olumlu etkileri belirlenmiş olup dikkat hafızave yürütücü işlevler gibi kognitif fonksiyonlar üzerindeki etkileri araştırılmaktadır. Bu çalışma üniversite öğrencilerinin fiziksel aktivite seviyeleri ile kognitif performansları arasındaki ilişkiyi incelemekamacıyla yapılmıştır. Bu amaç doğrultusunda yaşları 18-25 aralığında değişen 83 kişi ile testleryürütülmüştür. Fiziksel aktivite seviyelerinin tespitinde Uluslararası Fiziksel Aktivite Kısa Anketi (International Physical Activity Questionnare-IPAQ), kognitif performans seviyelerini belirlemedeyürütücü işlevleri içeren Stroop Testi TBAG Formu kullanılmış ayrıca demografik bilgilerkaydedilmiştir. Tüm analizlerde istatistiksel anlamlılık p<0.05 olarak kabul edilmiştir. ANOVA testisonucunda Stroop etkisi fenomeni uyumsuz koşulda tepki sürelerinin anlamlı olarak gecikmesi ilegözlemlenmiştir. Kontrol ve uyumlu koşulda tepki süreleri uyumsuz koşula göre daha hızlıdır. Fizikselaktivitenin Stroop efekte etkisi anlamlı bulunmamıştır. MET ile Stroop etkisi arasındaki ilişkiyebakıldığında MET arttıkça Stroop etkisinin azalma eğilimi gösterdiği gözlemlense de, bu ilişki anlamlıdeğildir. Çalışmamızda üniversite öğrencilerinin toplam fiziksel aktivite seviyeleri ile kognitif performansları arasında doğrusal bir ilişki tespit edilememiştir. Daha fazla sayıda katılımcının dahil edildiğidaha ileri araştırmalara ihtiyaç vardır.

Evidence-based positive effects of physical activity on many areas of health have been determined, and its effects on cognitive functions such as attention, memory and executive functions are investigated. This study was conducted to examine the relationship between university students' physical activity levels and their cognitive performance. For this purpose, tests were conducted with 83 people whose ages ranged from 18-25. The International Physical Activity Questionnare (IPAQ) was used to determine physical activity levels, and the Stroop Test TBAG Form, which includes executive functions to determine cognitive performance levels, and demographic information was recorded. IBM SPSS 21 package program was used in the data analysis of the study. Statistical significance was accepted as p <0.05 in all analyzes. As a result of the ANOVA test, the Stroop effect phenomenon was observed with a significant delay in reaction times in the incompatible condition. Response times in control and adaptive condition are faster than in non-compliant conditions. The effect of physical activity on the stroop effect is not significant. Considering the relationship between BAT and Stroop effect, it is observed that as the MET increases, the Stroop effect tends to decrease, but this relationship is not significant. In our study, no linear relationship was found between university students' total physical activity levels and their cognitive performance. Further research is needed, involving larger numbers of participants.
Investigation of the relationship between physical activity and cognitive performance in young adults
Keywords: Genç Yetişkin; Fiziksel Aktivite; Bilişsel Performans; Young Adults; Physical Activity; Cognitive Performance